There are no zeroes for an expression, only for equations.
Assuming equation to be
<span>−7x^2 − 91x − 280=0
-7(x^2+13x+40)=0
-7(x+8)(x+5)=0
by the zero product properties,
x+8=0 => x=-8
or
x+5=0 => x=-5</span>
Answer:
88.02 ft/s
Step-by-step explanation:
Angle with the horizontal, θ =25°
Initial velocity, v = 60 mph
1 mph = 1.467 ft/s
60 mph = 60 × 1.467 ft/s = 88.02 ft/s
Vertical component, v sin θ = 88.02 sin 25° = 37.2 ft/s
Horizontal component, v cos θ = 88.02 cos 25°= 79.8 ft/s
Answer:
3x^5y^6 (a)
Step-by-step explanation:
La raiz de un productor es igual al producto de las raices de cada factor
^4√81 ^4√x^20 ^4√y^24
escriba el numero en forma exponencial an base 3
^4√3^4 ^4√x^20 ^4√y^24
simplifica el indice de la raiz y el exponente usando 4
^4√3^4 x^5 ^4√y^24
simplifica el indice de la raiz y el exponente usando 4
^4√3^4 x^5 y^6
simplifica el indice de la raiz y el exponente usando 4
3x^5y^6
Answer:
28/55
Step-by-step explanation:
total no of beads are 11
red beads are 7
and white beads are 4
no of ways to take 2 beads from 11 beads are 11c2
that is( 11*10)/2=55
no of ways to take 1 red bead from 7 is 7c1 that is 7
no of ways to take 1 white bead from 4 is 4c1 is that is 4
required probability is( 7*4)/55=28/55
this question has already been answered on someone else's account so know this answer is 100% correct
hope that helped :)
The converse would be If x² = 100 then x = -10
So essentially if the conditional statement is p → q then the converse is q → p (In essence, the converse of a conditional statement is formed by interchanging the hypothesis and the conclusion.)